Effect of Black Coffee on Fasting Metabolic Markers and an Abbreviated Fat Tolerance Test. (29th May 2020) - Keirns, Bryant; Elliott, Destinee; Sciarrillo, Christina; Koemel, Nicholas; Poindexter, Kara; Emerson, Sam
Abstract: Objectives: Common clinical recommendations direct patients to report fasted when blood work (e.g., triglycerides [TG], glucose [Glu]) will take place, which typically excludes black coffee consumption. Despite its negligible calorie content, caffeinated coffee increases fatty acid mobilization. However, whether this effect meaningfully alters fasting metabolic testing or influences the results of a fat tolerance test is unclear. We investigated whether allowing black coffee intake within a fast prior to blood work affected fasting TG and Glu, as well as the postprandial lipemic and glycemic response following an abbreviated fat tolerance test. Methods: In a randomized crossover design, participants were instructed to consume only water, or were allowed 8 fluid ounces of black coffee at the end of a 10-hr fast. Next, TG and Glu were assessed using the Cholestech LDX system (Alere Cholestech: Hayward, CA, USA) before and after a previously validated 4-hr fat tolerance test (9 kcal/kg; 73% fat, 26% CHO). Paired t-tests were performed to assess baseline and 4-hr values, absolute change, and % change for both TG and Glu. Results: Preliminary analysis of healthy subjects ( n = 3 of 10 subjects completed; 1 M/2F; age 20.3 ± 2.3; BMI 25.7 ± 0.6) revealed that consuming coffee prior to the blood draw did not affect fasting TG (Mean difference (MD) = 7.0 mg/dL; P = 0.68). Similarly, the lipemic response was not altered by coffee, evidenced by no alterations in 4-hr TG (MD = 7.6 mg/dL), Δ TG (MD = 14.7 mg/dL), and % change in TG (MD = 29.1%; all P 's ≥ 0.52). Fasting Glu was unchanged following coffee consumption (MD = 29.1 mg/dL; P = 0.90), and indicators of the glycemic response such as 4-hr Glu (MD = 0.0 mg/dL), Δ Glu (MD = 1.0 mg/dL), and % change (MD = 1.2%), were similar among water and coffee trials (all P's ≥ 0.73) . Conclusions: At this point in the study, coffee consumption does not seem to alter fasting TG or markers of fat tolerance. Additionally, fasting Glu and the glycemic response do not appear to be influenced by coffee consumption. When completed, this study will help answer the practical question of whether coffee need be avoided prior to basic metabolic testing or a fat tolerance test, which may provide increased consistency in metabolic assessment and potentially improve patients' clinical experience. Funding Sources: Lew Wentz Research Scholars Program at Oklahoma State University.